TINDAK TUTUR ILOKUSI DALAM NOVEL RASA KARYA TERE LIYE - Puspita, Amelia; Patriantoro, Patriantoro; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
Language is a means of communivation between people one another. The language used will help humans communicate. Language is also found in novels in the form of speech in the form of conversations or dialog between characters. One of the novels that has a lot of speech is the novel Rasa by Tere Liye. Therefore, the researcher wants to know what illocutionary speech is contained in the novel Rasa by Tere Liye. This study adopted descriptive method and qualitative research form. The research data were obtained in the form of words, phrases and sentences of assertive, directive, commissive, expressive, and declarative illocutionary speech acts contained in Tere Liye